Balloon Assisted Transvenous Coil Embolization of Posttraumatic Direct Carotid-Cavernous Fistula with the Successful Outcome: A Case Report (Nepalese Journal of Radiology, 2024)
A carotid cavernous fistula (CCF) is an abnormal connection between the internal carotid artery and the cavernous sinus. This case pertains to a 19-year-old male who presented with left periorbital swelling following a road traffic accident and was found to have direct CCF on imaging. The patient underwent balloon-assisted transvenous embolization, with access to the fistula being gained through the femoral vein and the inferior petrosal sinus. The use of coils successfully blocked the fistula, leading to the resolution of symptoms without any complications. This case underscores the significance of a multidisciplinary approach and the effectiveness of balloon-assisted embolization.